New method for the growth of single-walled carbon nanotubes from bimetallic nanoalloy catalysts based on Prussian blue analog precursors. (October 2017) - Castan, A.; Forel, S.; Catala, L.; Florea, I.; Fossard, F.; Bouanis, F.; Andrieux-Ledier, A.; Mazerat, S.; Mallah, T.; Huc, V.; Loiseau, A.; Cojocaru, C.S.
Abstract: Catalyst engineering is a key point for selective growth of single-walled carbon nanotubes (SWCNT) with chemical vapor deposition (CVD). Here, we develop a new general synthesis method able to produce a wide range of homogenous bimetallic catalyst nanoparticles with controlled stoichiometry and sizes. The basics of this catalyst synthesis is to use preformed stoichiometric bimetallic Prussian blue analog (PBA) nanoparticles. Catalyst nanoparticles are then prepared in-situ in a hot filament CVD reactor with subsequent high temperature treatment in reducing atmosphere prior to SWCNT growth. The capabilities of the synthesis route are demonstrated by testing five PBA systems involving various transition metals. Transmission electron microscopy (TEM), scanning TEM and energy dispersive X-ray spectroscopy (STEM-EDX), and in-situ X-ray photoelectron spectroscopy (XPS) measurements are used to finely follow the size and composition of the catalyst at each step of the process. Each system yields small size catalysts with a narrow distribution, which act as efficient catalysts for SWCNT growth with a good yield and small diameter distribution. The versatility of the PBA family paves a new way for a fine tuning of the catalyst properties monitored by the metal involved in the PBA, and for opening routes to more selective SWCNT synthesis. Graphical abstract: